2014
DOI: 10.1007/s40271-014-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumers and Carers Versus Pharmacy Staff: Do Their Priorities for Australian Pharmacy Services Align?

Abstract: Overall, pharmacy staff had a reasonable understanding of what consumers would prioritise, but further emphasis on the importance, delivery, or both, of consumer information is needed. Greater consideration is needed from policy makers regarding the financial barriers to accessing medication for consumers with chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In Australia, consumers want pharmacies that provide patient-centered care, with convenience, prices and pharmacies that meet their expectations being additional factors 6. Australian pharmacists recognized the consumers’ desire for patient-centered care, accessibility, and continuity of care but did not realize their desire for information 3. This study suggests that English pharmacists’ perceptions also do not fully align with those of potential service users.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In Australia, consumers want pharmacies that provide patient-centered care, with convenience, prices and pharmacies that meet their expectations being additional factors 6. Australian pharmacists recognized the consumers’ desire for patient-centered care, accessibility, and continuity of care but did not realize their desire for information 3. This study suggests that English pharmacists’ perceptions also do not fully align with those of potential service users.…”
Section: Discussionmentioning
confidence: 82%
“…Examples of these are the home medicine review (HMR) service in Australia, medication therapy management services (MTM) in the US, and the medicines use review (MUR) and new medicines service (NMS) in England. While research has investigated the provision of these services from the perspectives of both pharmacists and users separately, relatively few studies have compared the views of pharmacists and potential service users 13. Studies in the US have explored the expectations of potential users of MTM and investigated the factors they view as important in selecting a pharmacy 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…These findings could indicate a lack of public knowledge and the need for further public education on access to medical records 41. Internationally, studies in Australia and the USA have reported that patients prefer pharmacists accessing their full medical record with links to their GP practice 42 43…”
Section: Discussionmentioning
confidence: 99%
“…The prioritisation study was undertaken as a three‐stage process involving a modified nominal group technique (NGT) with key stakeholders; an electronic Delphi (eDelphi) survey; and rationalisation of priority topics. The NGT and Delphi are commonly used in pharmacy practice research to achieve consensus . A modified NGT was used in this current study to generate topics in a fast and efficient manner during a face‐to‐face meeting.…”
Section: Methodsmentioning
confidence: 99%
“…The NGT and Delphi are commonly used in pharmacy practice research to achieve consensus. [15] A modified NGT was used in this current study to generate topics in a fast and efficient manner during a face-to-face meeting.…”
Section: Methodsmentioning
confidence: 99%